Posttraumatic Growth and Dyadic Adjustment among War Veterans and their Wives - Lahav, Yael; Kanat-Maymon, Yaniv; Solomon, Zahava (Frontiers in Psychology, 2017)
The controversy regarding the nature of posttraumatic growth includes two main competing claims: one which argues that posttraumatic growth reflects authentic positive changes and the other which argues that posttraumatic growth reflects illusory defenses. While the former might suggest that posttraumatic growth enhances intimacy and close relationships, the latter might imply that posttraumatic growth hinders interpersonal relations. The present study aimed to test these claims by investigating the association between posttraumatic growth and dyadic adjustment over time at both the individual and dyadic levels, and the potential role of posttraumatic stress symptoms. Former prisoners of war and comparable war veterans and their wives (n=229) were assessed twice, 30-31 (T1) and 35-38 (T2) years after the 1973 Yom Kippur War in Israel, with regard to posttraumatic growth, posttraumatic stress symptoms and dyadic adjustment. Results indicated that posttraumatic growth was associated with both elevated posttraumatic stress symptoms and low dyadic adjustment among both husbands and wives. Posttraumatic stress symptoms at T1 and T2 mediated the association between posttraumatic growth and dyadic adjustment. Wives' posttraumatic growth at T1 predicted posttraumatic growth and dyadic adjustment of the husbands at T2. The higher the wives' posttraumatic growth, the higher the posttraumatic growth and the lower the dyadic adjustment of the husbands in the subsequent measure. The findings suggest that posttraumatic growth reflects defensive beliefs which undermine marital relationships and that posttraumatic growth might be transmitted between spouses and implicated in the deterioration of the marital relationship over time.